2022
DOI: 10.1371/journal.pclm.0000008
|View full text |Cite
|
Sign up to set email alerts
|

Two sets of initial conditions on boreal forest carbon storage economics

Abstract: Two sets of initial conditions are used in the investigation of capital return rate and carbon storage in boreal forests. Firstly, a growth model is applied in young stands as early as the inventory-based model is applicable. Secondly, the growth model is applied to observed wooded stands. Four sets of thinning schedules are investigated in either case. The two sets of initial conditions yield similar results. The capital return rate is a weak function of rotation age, which results in variability in the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 48 publications
(95 reference statements)
10
29
0
Order By: Relevance
“…Figure 16 indicates that a significant excess volume can be produced at the expense of a monetary capital return rate deficiency in the order of one to two Euros/excess cubic meter per annum. This can be easily compensated by a carbon rent derived from European carbon emission prices valid at the time of writing [18,19,40]. On the other hand, such compensation is needed to achieve a large-scale increment in carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 16 indicates that a significant excess volume can be produced at the expense of a monetary capital return rate deficiency in the order of one to two Euros/excess cubic meter per annum. This can be easily compensated by a carbon rent derived from European carbon emission prices valid at the time of writing [18,19,40]. On the other hand, such compensation is needed to achieve a large-scale increment in carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such compensation is needed to achieve a large-scale increment in carbon sequestration. It has been recently shown that the carbon stock can be increased without deteriorating the wood supply for forest-based industries [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For climate change mitigation purposes, some institutions include carbon sequestration in their business strategies [27,28]. However, enhanced carbon sequestration generally induces a deficiency in the gained financial benefit [29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%